The Diophantine equation x2+2k=yn, II - J. H. E. Cohn (International Journal of Mathematics and Mathematical Sciences)
New results regarding the full solution of the diophantine equation x2+2k=yn in positive integers are obtained. These support a previous conjecture, without providing a complete proof.